Motivation and Employee Engagement Approach to the Performance of Inpatient Nurses - Hartono, Seno; Hartiti, Tri; Astuti, Rahayu (Media Keperawatan Indonesia, 2025)
Nurse performance in inpatient wards is a key factor in determining the quality of hospital services. Effective motivation and employee engagement are crucial strategies for improving employee morale and loyalty. The objective of the research is to analyze the influence of work motivation and employee engagement levels on nurse performance in the inpatient wards of a Regional Public Hospital (RSUD). This research used the quasi-experimental pre-post test with a control group design, where the intervention group was given motivation training for 2 days, modules, and mentoring, while the control group was only given modules, with a total sample of 160, 80 nurse respondents in the intervention group, and 80 nurse respondents in the control group. Data analysis using paired sample T-tests and independent sample T-tests. There is a difference in the average increase in nurse performance before and after being given employee engagement motivation (p-value = 0.000). There is a difference in the increase in nurse performance after being given training, modules, and motivational mentoring in the intervention group of 35.36 compared to the control group given the motivation module of 11.1 (p-value = 0.000). meaning there is a significant influence after being given employee engagement motivation training on improving nurse performance in the intervention group. Nurse motivation and employee engagement in providing nursing care are effective in improving the performance of inpatient ward nurses in hospitals.